Tratamiento de agua residual procedente de lavadoras por el método de electrocoagulación para la reutilización en riego de vegetales – Ate Vitarte - Cuba Tello, María Vanessa (2019)
Electrocoagulation (EC) in recent years is calling the growing attention for the elimination of different contaminants present in the various effluents. Through this work, the feasibility of using the electrocoagulation technique as an alternative to conventional chemical processes in the treatment of wastewater from washing machines to be reused in vegetable irrigation, analyzed regularly was verified. Four factors were analyzed: intensity, time, distance and pH; with three levels for each factor. To optimize the electrocoagulation process on the design factors, the experiments were carried out according to the Taguchi method. The analysis of variance (ANOVA) was performed to see the effect of the variables on the removal of turbidity and other physicochemical parameters. The results showed that the parameters with the greatest influence on the removal of turbidity were time and intensity compared to the others. The optimization of the factors on the high removal of the physicochemical parameters was obtained at the levels of intensity 5 Amps, time of 15 minutes, distance of 2 centimeters and pH 7.5, with a removal of 99.02% in turbidity, 90.83% in COD Y 95.93% in SST, with which the treated effluent is in the permissible range for use in vegetable irrigation.